Implementation of the International Primary Curriculum (IPC): Strengthening 21st-Century Skills and Contributing to Sustainable Development Goals in Indonesia - Adzillah, Salasabila Nur Imatul; Sitorus, Adnan Syah; Alifia, Larasati Husna (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study aims to analyze the implementation of the International Primary Curriculum (IPC) in supporting 21st century education through strengthening critical thinking, creativity, communication, and collaboration (4C) skills, as well as evaluating its contribution to the achievement of the Sustainable Development Goals (SDGs), especially Goal 4: Quality Education. The method used is Systematic Literature Review (SLR) with the PRISMA approach, which involves searching the literature on the Scopus database, Google Scholar, and the Publish or Perish tool for the period 2020–2025. The results show that IPC significantly improves 4C skills through thematic, cross-disciplinary, and project-based learning that encourages student engagement, knowledge transfer, and an in-depth understanding of global and local issues. IPC's contribution is also seen in strengthening the principles of inclusivity, integrating sustainability values, and adapting learning that is relevant to the cultural context, so that it is in line with the SDGs agenda. However, the main challenges in its implementation in Indonesia include disparities in educational infrastructure, limited teacher capacity, and resource gaps between regions. The implications of this study underscore the importance of policy strategies that emphasize improving teacher competence, adapting the curriculum to local contexts, and collaboration between stakeholders to ensure sustainable implementation. Follow-up studies are recommended to explore the effectiveness of IPC implementation through field studies, longitudinal analysis of student learning outcomes, and evaluation of teacher training programs to strengthen the relevance and competitiveness of basic education in Indonesia.